HUBUNGAN CUSTOMER RELATIONSHIP MANAGEMENT DENGAN LOYALITAS PASIEN RAWAT JALAN DI RSUD LABUANG BAJI MAKASSAR TAHUN 2023 - Sitti Aisyah; Nur Mulia Wunanini Ngkolu; Sriyani Windarti; Reski Dewi Pratiwi (Institut Kesehatan Pelamonia, 2025)
The decline in the number of outpatient visits at Labuan Baji Hospital Makassar from year to year cannot be ignored by the hospital, therefore the hospital needs to pay attention to factors that can affect patient loyalty, one of which is by implementing customer relationship management. This study aims to determine the relationship between customer relationship management (CRM) and outpatient loyalty at Labuan Baji General Hospital Makassar in 2023.The type of research used is quantitative research with a cross-sectional study design. The population in this study was 863 people, then the sample was obtained using the slovin formula, namely 273 people and the sampling technique was using accidental sampling. Data analysis used was univariate, bivariate with chi-square test, and multivariate analysis with logistic regression. The results of this study indicate that there is a significant relationship between people (p=0.035), process (p=0.011), knowledge and insight (p=0.001) and patient loyalty. While technology is not related to patient loyalty with a value (p = 0.315), then the variables most related to patient loyalty are knowledge and insight. It is hoped that the hospital will maintain, maintain and improve the implementation of customer relationship management so that it is able to maintain and increase the number of loyal patients.